Intervención de enfermería en paciente de sexo masculino de 14 años de edad con celulitis en miembro inferior derecho. - Rivas Chiliquinga, Sara Isabel (2020)
Cellulitis is an acute bacterial infection involving the skin and subcutaneous tissue, it is generally caused by causative agents such as streptococci or staphylococci. The clinical manifestations are pain, heat, edema, erythema, fever, it becomes more serious infections when the regional lymph nodes increase in size. Cultures are helpful for diagnosis, but antibiotic treatment should not be delayed. The prognostic factor is optimal with proper treatment of the lesions. The current clinical case was based on the nursing interventions used in a 14 year old male patient with a diagnosis of cellulitis in the lower right limb.